A CASE REPORT ON ZYGOMATIC ABSCESS: OUR EXPERIENCE. - Arunima VS,; Chatterjee , Dr. Chandrani; Hetal Marfatia,; Pranita Bhagat, (Student's Journal of Health Research Africa, 2023)
To study the various etiologies of zygomatic abscess, its clinical presentations and management in different situations. Zygomatic abscess commonly occurs as a complication of chronic suppurative otitis media, but it may even present as primary infection of zygomatic bone. We have studied six cases of zygomatic abscess, who presented with varied presentation to our OPD in the last 18 months. Two patients presented with primary tuberculosis of zygomatic bone with normal aerated mastoid. Two presented with zygomatic abscess secondary to TB mastoiditis. Rest 33% had zygomatic abscess secondary to chronic suppurative otitis media with active squamosal disease. Appropriate investigations for diagnosing the primary cause of zygomatic abscess is essential for complete cure of the condition. In developing countries, where most of the population belonging to middle and low socioeconomic status, tuberculosis must be kept in mind as a DD.